Is Scientific Learning Better Than Conventional Learning on Creativity and Student Learning Outcomes? - Albadi Sinulingga; Sabaruddin Yunis Bangun; Wicaksono Wicaksono (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2023)
This study aims to identify and describe the Comparison of the Effects of Scientific and Conventional Learning on the Creativity and Learning Outcomes of Physical Education Students in Class XI SMA in Kota Kisaran, Kab. Asahan T.A 2017/2018. This study was an experiment using test instrument techniques for learning outcomes and questionnaires for creativity, with the ANOVA 2 x 2 research design. A total of 138 students were sampled using cluster random sampling sampling technique. Before carrying out a two-way analysis of variance at a significance level of α of 0.05, first perform the analysis requirements, namely the normality and homogeneity tests, followed by the Scheffe test at a significance level of α = 0.05. Research results: 1). There are differences in learning the effect of learning on creativity and learning outcomes, 2). There is an interaction between the influence of learning on creativity and physical education learning outcomes. From the results of this study indicate that the process of applying scientific learning is better in achieving physical education learning outcomes compared to the application of conventional learning.